Pengaruh Kompetensi dan Motivasi Kerja Perawat terhadap Kualitas Pelayanan Kesehatan pada Rumah Sakit Umum Daerah Prof. Dr. Aloe Saboe Kota Gorontalo - Asral Kelvin Sahrain (Scimadly Publishing, 2022)
This study aims to: (1). To analyze the effect of the competence variable on the quality of health services at the Prof. Regional General Hospital. Dr.H.Aloei Saboe, Gorontalo City, (2). To analyze the effect of the variable work motivation of nurses on the quality of health services at the Regional General Hospital, Prof. Dr.H.Aloei Saboe, Gorontalo City, (3). to analyze the effect of the competence and work motivation of nurses simultaneously on the quality of health services at the Prof. Regional General Hospital. Dr. H. Aloei Saboe, Gorontalo City. The results of testing the first hypothesis indicate that there is an insignificant effect with a weak regression level between competence and quality of health services, testing the second hypothesis shows that there is a significant relationship with a fairly strong correlation level between nurses' work motivation and the quality of health services, testing the third hypothesis shows that there is a simultaneous and significant influence between the competence and work motivation of nurses on the quality of health services. So it is clear that although the work motivation of nurses has a dominant influence, competence and work motivation are an integral part that need to be considered by the hospital because they simultaneously have a significant influence in improving the quality of health services at the Blood General Hospital Prof. Dr. Aloe Saboe Gorontalo City.